FISIOLOGI BUI DORMAN GEWANG (Corypha Man Lamarck) - BP Naiola (BERITA BIOLOGI, 2007)
Gewang (Corypha utan Lamarck), a wild or semi-wild palm species distribute widely in Nusa Tenggara savanna with great potential(as building materials, drink and food), as traditionally have been exploited and utilized by local villagers for ages.To increase her potential should be promoted by plant domestication applied as on farm model such as agroforestry and social forestry. Seedlings availability is one of the basic need when comes to plant domestication. The only possibility of propagation in gewang is by generative phase (seeds). On the other hand, gewang seeds are known as orthodox, with low percentage of germination. This study shows that mature gewang seeds dropped under the mother trees are highly protected by tight tissues of endocarp and endosperm. Although the mature seeds in the nature seems ready to germinate, however there should be a dimensional balance (chemical, physical and physiological) or synchronization among components (endocarp/testa, endosperm and embryo) as a driving force to promote germination.In nature, the attainment of this synchronization/ dimensional balance of gewang seeds, are driven by external (both biotic and abiotic) factors as well such as fungi and climatic fluctuations. While artificial treatments like scarification, soaking, heating and acid are to accelerate the dimensional balance. Low embryo content per 100 seeds also responsible for low seed germination. It is suggested that low embryo content may be due to interactions among factors like low fertility of pollen grains, time incompatibility between gynoecium (stigma) and androecium (pollen grains) during pollen shed process and ineffectiveness of pollination due to great number of flowers.